Mindful breathing for cancer pain : efficacy of a single 20-minute session – a randomised controlled study - Tan, Seng Beng; Chai, Chee Shee; Diana Ng, Leh Ching; Sheriza Izwa, Zainuddin; David Paul, Capelle; Lam, Chee Loong; Ang, Chui Munn; Chai, Win Lin; Nik Natasha, Nik Ishak; Ong, Yu Xiang; Ngu, Ying Xi (BMJ Publishing Group Ltd, 2024)
Objectives Cancer pain is a prevalent and challenging symptom affecting a significant number of patients globally, with inadequate control remaining a substantial challenge despite advancements in pain management. Non-pharmacological interventions, including mindfulness-based approaches, have shown promise in alleviating cancer-related pain. This study aimed to explore the efficacy of a single session of 20-minute mindful breathing in reducing pain among patients with cancer. Methods A randomised controlled study was conducted at the University of Malaya Medical Centre, Malaysia, involving adult cancer inpatients with a pain score of ≥4/10. Participants were randomly assigned to a 20-minute mindful breathing intervention or a 20-minute supportive listening control group. Outcome measures included pain intensity, pain unpleasantness and Hospital Anxiety and Depression Scale score, assessed before and after the intervention. Results The 20-minute mindful breathing sessions demonstrated significant efficacy in reducing pain intensity, pain unpleasantness and anxiety compared with the control group. Conclusion This research broadens the repertoire of cancer pain management by highlighting the rapid and holistic benefits of a single session of 20-minute mindful breathing. The findings suggest the potential integration of brief mindfulness exercises into routine cancer care to enhance pain management and overall well-being